Insect Pests of Agroforestry Leguminous Trees in India - Vir, Satya; Verma, S K (Annals of Arid Zone, 2016)
This paper attempts to document the recorded arthropod pest species associated with leguminous agroforestry trees in India. The list also covers casual feeders. The compilation, from various sources including published and unpublished reports, notes, and our surveys,etc., will be of immense help to ascertain about future new records.